NEW
New Website Launch
Experience the best way to solve previous year questions with mock tests (very detailed analysis), bookmark your favourite questions, practice etc...
1

WB JEE 2022

MCQ (Single Correct Answer)
English
Bengali

If $$\overrightarrow a = \widehat i + \widehat j - \widehat k$$, $$\overrightarrow b = \widehat i - \widehat j + \widehat k$$ and $$\overrightarrow c $$ is unit vector perpendicular to $$\overrightarrow a $$ and coplanar with $$\overrightarrow a $$ and $$\overrightarrow b $$, then unit vector $$\overrightarrow d $$ perpendicular to both $$\overrightarrow a $$ and $$\overrightarrow c $$ is

A
$$ \pm {1 \over {\sqrt 6 }}\left( {2\widehat i - \widehat j + \widehat k} \right)$$
B
$$ \pm {1 \over {\sqrt 2 }}\left( {\widehat j + \widehat k} \right)$$
C
$$ \pm {1 \over {\sqrt 6 }}\left( {\widehat i - 2\widehat j + \widehat k} \right)$$
D
$$ \pm {1 \over {\sqrt 2 }}\left( {\widehat j - \widehat k} \right)$$

দেওয়া আছে $$\overrightarrow a = \widehat i + \widehat j - \widehat k$$, $$\overrightarrow b = \widehat i - \widehat j + \widehat k$$, $$\overrightarrow c $$ একটি একক ভেক্টর $$\overrightarrow a $$ এর উপর লম্ব এবং $$\overrightarrow a $$ ও $$\overrightarrow b $$ এর সঙ্গে একতলীয়। সেক্ষেত্রে $$\overrightarrow a $$ ও $$\overrightarrow c $$ উভয়ের উপর লম্ব ও একক ভেক্টর $$\overrightarrow d $$ হবে

A
$$ \pm {1 \over {\sqrt 6 }}\left( {2\widehat i - \widehat j + \widehat k} \right)$$
B
$$ \pm {1 \over {\sqrt 2 }}\left( {\widehat j + \widehat k} \right)$$
C
$$ \pm {1 \over {\sqrt 6 }}\left( {\widehat i - 2\widehat j + \widehat k} \right)$$
D
$$ \pm {1 \over {\sqrt 2 }}\left( {\widehat j - \widehat k} \right)$$
2

WB JEE 2021

MCQ (Single Correct Answer)
English
Bengali
If a($$\alpha$$ $$\times$$ $$\beta$$) + b($$\beta$$ $$\times$$ $$\gamma$$) + c($$\gamma$$ + $$\alpha$$) = 0, where a, b, c are non-zero scalars, then the vectors $$\alpha$$, $$\beta$$, $$\gamma$$ are
A
parallel
B
non-coplanar
C
coplanar
D
mutually perpendicular

Explanation

We have,

a($$\alpha$$ $$\times$$ $$\beta$$) + b($$\beta$$ $$\times$$ $$\gamma$$) + c($$\gamma$$ + $$\alpha$$) = 0

Clearly a($$\alpha$$ $$\times$$ $$\beta$$), ($$\beta$$ $$\times$$ $$\gamma$$) and ($$\gamma$$ + $$\alpha$$) are coplanar vector $$\therefore$$ $$\alpha$$, $$\beta$$ and $$\gamma$$ are also coplanar.
দেওয়া আছে a($$\alpha$$ $$\times$$ $$\beta$$) + b($$\beta$$ $$\times$$ $$\gamma$$) + c($$\gamma$$ + $$\alpha$$) = 0, যেখানে a, b, c অশূণ্য স্কেলার। সেক্ষেত্রে $$\alpha$$, $$\beta$$, $$\gamma$$ ভেক্টরত্রয়
A
পরস্পর সমান্তরাল
B
সমতলীয় নয়
C
সমতলীয়
D
পরস্পর লম্ব

Explanation

আমাদের কাছে,

a($$\alpha$$ $$\times$$ $$\beta$$) + b($$\beta$$ $$\times$$ $$\gamma$$) + c($$\gamma$$ + $$\alpha$$) = 0

স্পষ্টতই a($$\alpha$$ $$\times$$ $$\beta$$), ($$\beta$$ $$\times$$ $$\gamma$$) এবং ($$\gamma$$ + $$\alpha$$) হল সমতলীয় ভেক্টর

$$\therefore$$ এছাড়াও $$\alpha$$, $$\beta$$ and $$\gamma$$ হল সমতলীয়.
3

WB JEE 2021

MCQ (Single Correct Answer)
English
Bengali
let $$\alpha$$, $$\beta$$, $$\gamma$$ be three non-zero vectors which are pairwise non-collinear. if $$\alpha$$ + 3$$\beta$$ is collinear with $$\gamma$$ and $$\beta$$ + 2$$\gamma$$ is collinear with $$\alpha$$ then $$\alpha$$ + 3$$\beta$$ + 6$$\gamma$$ is
A
$$\gamma$$
B
0
C
$$\gamma$$ + $$\gamma$$
D
$$\alpha$$

Explanation

Given, $$\alpha$$ + 3$$\beta$$ is collinear with $$\gamma$$

$$\therefore$$ $$\alpha$$ + 3$$\beta$$ = $$\lambda$$$$\gamma$$ ...... (1)

and $$\beta$$ + 2$$\gamma$$ is collinear with $$\alpha$$

$$\therefore$$ $$\beta$$ + 2$$\gamma$$ = $$\mu$$$$\alpha$$ ...... (2)

Add 6$$\gamma$$ with equation (1), we get

$$\alpha$$ + 3$$\beta$$ + 6$$\gamma$$ = (6 + $$\lambda$$)$$\gamma$$ ...... (3)

Multiply equation (2) with (3) and add $$\alpha$$, we get

$$\alpha$$ + 3$$\beta$$ + 6$$\gamma$$ = (3$$\mu$$ + 1)$$\alpha$$ ..... (4)

From (3) and (4), we get

(6 + $$\lambda$$)$$\gamma$$ = (3$$\mu$$ + 1)$$\alpha$$ ..... (5)

As, $$\alpha$$, $$\beta$$, $$\gamma$$ are not pairwise collinear so in equation (5) coefficient of $$\gamma$$ and $$\alpha$$ must be zero.

$$\therefore$$ 6 + $$\lambda$$ = 0 and 3$$\mu$$ + 1 = 0

$$\therefore$$ From equation (3),

$$\lambda$$ + 3$$\beta$$ + 6$$\gamma$$ = (6 + $$\lambda$$)$$\gamma$$ = 0 $$\times$$ $$\gamma$$ = 0

মনে কর $$\alpha$$, $$\beta$$, $$\gamma$$ তিনটি অ-শূণ্য ভেক্টর যাদের মধ্যে কোন দুটি একযােগে সমরেখ নয়। যদি $$\alpha$$ + 3$$\beta$$ ও $$\gamma$$ সমরেখ হয় এবং $$\beta$$ + 2$$\gamma$$ ও $$\alpha$$ সমরেখ হয়, তবে $$\alpha$$ + 3$$\beta$$ + 6$$\gamma$$ হবে
A
$$\gamma$$
B
0
C
$$\gamma$$ + $$\gamma$$
D
$$\alpha$$

Explanation

প্রদত্ত, $$\alpha$$ + 3$$\beta$$, $$\gamma$$-এর সাথে সমরেখ

$$\therefore$$ $$\alpha$$ + 3$$\beta$$ = $$\lambda$$1$$\gamma$$

$$\Rightarrow$$ $$\beta = {{{\lambda _1}} \over 3}\gamma - {\alpha \over 3}$$ .... (i)

এবং $$\beta$$ + 2$$\gamma$$ হল $$\alpha$$-এর সাথে সমরেখ

$$\therefore$$ $$\beta$$ + 2$$\gamma = \lambda$$2$$\alpha$$

$$\Rightarrow$$ $$\beta$$ = $$\lambda$$2$$\alpha$$ $$-$$ 2$$\gamma$$ ...... (ii)

সমীকরণ (i) এবং (ii) থেকে, আমরা পাই

$${{{\lambda _1}} \over 3}\gamma - {\alpha \over 3} = {\lambda _2}\alpha - 2\gamma $$

$$ \Rightarrow \alpha \left( {{\lambda _2} + {1 \over 3}} \right) = \gamma \left( {{{{\lambda _1}} \over 3} + 2} \right)$$

$$ \Rightarrow {\lambda _2} + {1 \over 3} = 0$$ এবং $${{{\lambda _1}} \over 3} + 2 = 0$$

$$ \Rightarrow {\lambda _2} = - {1 \over 3}$$ এবং $${{{\lambda _1}} \over 3} = - 2$$

$$ \Rightarrow {\lambda _1} = - 6$$ এবং $${\lambda _2} = - {1 \over 3}$$

সমীকরণ (i) এবং (ii) থেকে, $$\beta = - 2\gamma - {\alpha \over 3}$$

$$\therefore$$ $$\alpha + 3\beta + 6\gamma = \alpha + 3\left( { - 2\gamma - {\alpha \over 3}} \right) + 6\gamma $$

$$ = 0$$
4

WB JEE 2020

MCQ (Single Correct Answer)
English
Bengali
The unit vector in ZOX plane, making angles $$45^\circ $$ and $$60^\circ $$ respectively with $$\alpha = 2\widehat i + 2\widehat j - \widehat k$$ and $$\beta = \widehat j - \widehat k$$ is
A
$${1 \over {\sqrt 2 }}\widehat i + {1 \over {\sqrt 2 }}\widehat j$$
B
$${1 \over {\sqrt 2 }}\widehat i - {1 \over {\sqrt 2 }}\widehat k$$
C
$${1 \over {\sqrt 2 }}\widehat i - {1 \over {\sqrt 2 }}\widehat j$$
D
$${1 \over {\sqrt 2 }}\widehat i + {1 \over {\sqrt 2 }}\widehat k$$

Explanation

Let the unit vector in ZOX plane be

$$a = x\widehat i + z\widehat k,\left| a \right| = 1$$

$$a.\alpha = \left| a \right|\left| \alpha \right|\cos 45^\circ $$

$$ \Rightarrow $$ $$(x\widehat i + z\widehat k).(2\widehat i + 2\widehat j - \widehat k) = 1 \times 3 \times {1 \over {\sqrt 2 }}$$

[$$ \because $$ $$\alpha = 2\widehat i + 2\widehat j - \widehat k$$]

$$2x - z = {3 \over {\sqrt 2 }}$$

and $$a.\beta = \left| a \right|\left| \beta \right|\cos 60^\circ $$

$$ \Rightarrow (x\widehat i + z\widehat k).(\widehat j - \widehat k) = 1 \times \sqrt 2 \times {1 \over 2}$$ [$$ \because $$ $$\beta = \widehat j - \widehat k$$]

$$ - z = {1 \over {\sqrt 2 }}$$

$$z = - {1 \over {\sqrt 2 }}$$ and $$x = {1 \over {\sqrt 2 }}$$

$$ \therefore $$ $$a = {1 \over {\sqrt 2 }}\widehat i - {1 \over {\sqrt 2 }}\widehat k$$

ZOX তলে একক ভেক্টর যথাক্রমে 45$$^\circ$$ ও 60$$^\circ$$ কোণ উৎপন্ন করে $$\overrightarrow \alpha $$ ও $$\overrightarrow \beta $$ এর সঙ্গে যেখানে $$\overrightarrow \alpha = 2\widehat i + 2\widehat j - \widehat k$$ এবং $$\overrightarrow \beta = \widehat j - \widehat k$$। সেক্ষেত্রে উক্ত একক ভেক্টরটি হবে

A
$${1 \over {\sqrt 2 }}\widehat i + {1 \over {\sqrt 2 }}\widehat j$$
B
$${1 \over {\sqrt 2 }}\widehat i - {1 \over {\sqrt 2 }}\widehat k$$
C
$${1 \over {\sqrt 2 }}\widehat i - {1 \over {\sqrt 2 }}\widehat j$$
D
$${1 \over {\sqrt 2 }}\widehat i + {1 \over {\sqrt 2 }}\widehat k$$

Explanation

একক ভেক্টরটি $$\overrightarrow A = a\widehat i + b\widehat k$$ হলে $$\left| {\overrightarrow A } \right| = \sqrt {{a^2} + {b^2}} = 1$$

$$\overrightarrow \alpha \,.\,\overrightarrow A = 2a - b = \left| {\overrightarrow \alpha } \right|\left| {\overrightarrow A } \right|\cos 45^\circ = {3 \over {\sqrt 2 }}$$

$$\overrightarrow \beta \,.\,\overrightarrow A = - b = \left| {\overrightarrow \beta } \right|\left| {\overrightarrow A } \right|\cos 60^\circ = \sqrt 2 .{1 \over 2} = {1 \over {\sqrt 2 }}$$

$$\therefore$$ $$b = - {1 \over {\sqrt 2 }}$$ এবং $$2a = {3 \over {\sqrt 2 }} + b = \sqrt 2 \Rightarrow a = {1 \over {\sqrt 2 }}$$

$$\therefore$$ $$\overrightarrow A = {1 \over {\sqrt 2 }}\widehat i - {1 \over {\sqrt 2 }}\widehat k$$

Joint Entrance Examination

JEE Main JEE Advanced WB JEE

Graduate Aptitude Test in Engineering

GATE CSE GATE ECE GATE EE GATE ME GATE CE GATE PI GATE IN

Medical

NEET

CBSE

Class 12